The Tale of Mr. Jeremy Fisher - Potter, Beatrix (London Frederick Warne & Co., 2011)
Mr. Jeremy has a day full of the worst fisherman's mishaps when he sets out to catch minnows for his dinner.
Keywords: Animals -- Children's Story